1989
DOI: 10.1038/bjc.1989.38
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of porphyrins with different tumour localising ability among human plasma proteins

Abstract: and 2University of Leeds, UK.Summary The distribution among the main fractions of human plasma lipoproteins of a number of porphyrins with different tumour localising ability has been determined by means of ultracentrifugation. A main trend is that the fraction of the dyes that are bound to low density lipoprotein (LDL) increases, and the fraction bound to HSA decreases with decreasing polarity of the dyes. An asymmetric charge distribution, such as in TPPS2a, favours LDL-binding more than expected on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 25 publications
3
58
0
1
Order By: Relevance
“…These investigators concluded that a non-specific LDL-Photofrin II uptake was involved in addition to the LDL receptor-mediated pathway. They later proposed that non-specific exchange of porphyrins between LDL and the plasma membrane occurs (Maziere et al, 1990 (Jori, 1989;Kongshaug et al, 1989). Thus, the nature of the association of BPD and Photofrin II with LDL may differ, especially since Photofrin II consists of an aggregated mixture of compounds (Dougherty et al, 1987;Kessel et al, 1987), most of which are not highly hydrophobic.…”
Section: '4c]bpd-ldl Accumulation By Cultured M-j Tumour Cellsmentioning
confidence: 99%
“…These investigators concluded that a non-specific LDL-Photofrin II uptake was involved in addition to the LDL receptor-mediated pathway. They later proposed that non-specific exchange of porphyrins between LDL and the plasma membrane occurs (Maziere et al, 1990 (Jori, 1989;Kongshaug et al, 1989). Thus, the nature of the association of BPD and Photofrin II with LDL may differ, especially since Photofrin II consists of an aggregated mixture of compounds (Dougherty et al, 1987;Kessel et al, 1987), most of which are not highly hydrophobic.…”
Section: '4c]bpd-ldl Accumulation By Cultured M-j Tumour Cellsmentioning
confidence: 99%
“…As a drug carrier, a protein may aid in the selective delivery of porphyrins to a tumour region and, as suggested for the lipoproteins, may facilitate drug access into the cell via receptor mechanisms (Jori et al, 1984;Reyftmann et al, 1984;Kessel, 1986a, Beltramini et al, 1987Kongshaug et al, 1989). On the other hand, the same carrier may cause a decrease in the amount of porphyrin available for PDT, by its rapid removal from the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of serum albumin and serum lipoproteins for porphyrins (Muller-Eberhard & Morgan, 1975;Morgan et al, 1980;Lamola et al, 1981 ;Reddi et al, 1981;Smith & Neuschatz, 1983;Grossweiner & Goyal, 1984;Jori et al, 1984;Reyftmann et al, 1984;Moan et al, 1985;Kessel, 1986a;Beltramini et al, 1987;Rotenberg et al, 1987;Kongshaug et al, 1989) indicates a role for these proteins as endogenous carriers of porphyrins administered for PDT (Kessel, 1985;Pottier & Truscott, 1986;Potter et al, 1987;Manyak et al, 1988). As a drug carrier, a protein may aid in the selective delivery of porphyrins to a tumour region and, as suggested for the lipoproteins, may facilitate drug access into the cell via receptor mechanisms (Jori et al, 1984;Reyftmann et al, 1984;Kessel, 1986a, Beltramini et al, 1987Kongshaug et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics and biodistribution studies conducted with PSs having different chemical structures and physical properties indicated that the extent and rate of PS accumulation in the tumor and the clearance from the body depends on several factors whose relative importance may vary considering different PSs of the families mentioned above [21,33]. It is, however, believed that, following intravenous administration, hydrophobic PSs are in general bound and transported in the bloodstream by lipoproteins, and low-density lipoproteins (LDL) are particularly important since they enhance specific accumulation in the cancer cells via LDL receptor-mediated endocytosis [34][35][36]. In fact it has been shown that many types of cancer cells overexpress LDL receptors to satisfy their need of cholesterol for the synthesis of membranes [37].…”
Section: Ideal Properties Of Photosensitizers For Pdtmentioning
confidence: 99%